Exploding the Realism-Antirealism Debate: Putnam contra Putnam. (15th September 2020) - Macarthur, David
Abstract: Putnam is famous (or infamous) for often changing his allegiance between various forms of realism and antirealism. In this paper I want to use Putnam's own reflections and insights on the realism-antirealism issue to provide a powerful case for skepticism about the entire debate—in spite of the fact that that is not Putnam's own ultimate attitude. From this skeptical perspective, I shall argue that Putnam has helped us see that the realism-antirealism debate faces a dilemma: either it resolves into existence questions about particular items that are resolvable by, say, scientific or mathematical or ethical etc. practices rather than by appeal to philosophical argument; or it represents a misguided response to skepticism about an entire class or realm of items (e.g., the unobservable items posited by physics, or the manifest world of tables and chairs) given that it hopelessly attempts to answer skepticism on the skeptic's own terms. What Putnam tends to overlook in his realist moments is that we can philosophically undermine skepticism without being committed to any philosophically substantial realism or antirealism.